Alteration of Synaptic Network Dynamics by the Intellectual Disability Protein PAK3 - Dubos, Aline (J Neurosci, 2012)
Several gene mutations linked to intellectual disability in humans code for synaptic molecules implicated in small GTPase signaling. This is the case of the Rac/Cdc42 effector p21-activated kinase 3 (PAK3). The mechanisms responsible for the intellectual defects and the consequences of the mutation on the development and wiring of brain networks remain unknown. Here we show that expression of PAK3 mutants, suppression of PAK3, or inhibition of PAK3 function in rat hippocampal slice cultures interfere with activity-mediated spine dynamics. Inhibition of PAK3 resulted in two main alterations: (1) an increased growth of new, unstable spines, occurring in clusters, and mediated by activity; and (2) an impairment of plasticity-mediated spine stabilization interfering with the formation of persistent spines. Additionally, we find that PAK3 is specifically recruited by activity from dendrites into spines, providing a new mechanism through which PAK3 could participate in the control of both spine stabilization and local spine growth. Together, these data identify a novel function of PAK3 in regulating activity-mediated rearrangement of synaptic connectivity associated with learning and suggest that defects in spine formation and refinement during development could account for intellectual disability.